2021
DOI: 10.1186/s43019-020-00076-x
|View full text |Cite
|
Sign up to set email alerts
|

Change of joint-line convergence angle should be considered for accurate alignment correction in high tibial osteotomy

Abstract: Background The alignment correction after high tibial osteotomy (HTO) is made both by bony correction and soft-tissue correction around the knee. Change of the joint-line convergence angle (JLCA) represents the soft-tissue correction after HTO, which is the angle made by a tangential line between the femoral condyles and the tibial plateau. We described the patterns of JLCA change and related factors after HTO and investigated the appropriate preoperative planning method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
0
37
1
Order By: Relevance
“…9 Most of these correction errors may be due to changes in soft tissue laxity. 20,21 Lee et al 16 investigated the disparity between the preoperative target correction amount and postoperative correction amount. They concluded that if the planned osteotomy gap was large, there was a mismatch between the targeted alignment and corrected alignment, and this mismatch did not deviate toward over- or undercorrection.…”
Section: Discussionmentioning
confidence: 99%
“…9 Most of these correction errors may be due to changes in soft tissue laxity. 20,21 Lee et al 16 investigated the disparity between the preoperative target correction amount and postoperative correction amount. They concluded that if the planned osteotomy gap was large, there was a mismatch between the targeted alignment and corrected alignment, and this mismatch did not deviate toward over- or undercorrection.…”
Section: Discussionmentioning
confidence: 99%
“…High tibial osteotomy (HTO) is an established and proven surgical method for medial compartmental OA with varus deformity [ 1 , 2 ]. Among HTO techniques, medial opening wedge HTO (MOWHTO) has become more popular than closing wedge HTO in recent years because of the simplicity of surgery [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has been reported to have good long-term clinical outcomes such as reduced pain and improved knee joint function [ 5 , 6 , 7 ]. Previous studies on MOWHTO tended to focus mainly on the change of alignment in the coronal plane regarding correction angle and postoperative coronal realignment [ 8 , 9 , 10 ]. However, MOWHTO is the three-dimensional (3D) surgical procedure.…”
Section: Introductionmentioning
confidence: 99%